Clostridium Septicum Encephalitis: A Case Report - Calabek, Bernadette; Hinterholzer, Georg; Neuwirth-Senautka, Gabriele; Kirschner, Harald; Horvath-Mechtler, Barbara; Grisold, Wolfgang (IntechOpen, 2011)
None